Control of the Anterior Pituitary Cell Lineage Regulator POU1F1 by the Stem Cell Determinant Musashi - Allensworth-James, Melody (Endocrinology, 2020)
The adipokine leptin regulates energy homeostasis through ubiquitously expressed leptin receptors. Leptin has a number of major signaling targets in the brain, including cells of the anterior pituitary (AP). We have previously reported that mice lacking leptin receptors in AP somatotropes display growth hormone (GH) deficiency, metabolic dysfunction, and adult-onset obesity. Among other targets, leptin signaling promotes increased levels of the pituitary transcription factor POU1F1, which in turn regulates the specification of somatotrope, lactotrope, and thyrotrope cell lineages within the AP. Leptin’s mechanism of action on somatotropes is sex dependent, with females demonstrating posttranscriptional control of Pou1f1 messenger RNA (mRNA) translation. Here, we report that the stem cell marker and mRNA translational control protein, Musashi1, exerts repression of the Pou1f1 mRNA. In female somatotropes, Msi1 mRNA and protein levels are increased in the mouse model that lacks leptin signaling (Gh-CRE Lepr-null), coincident with lack of POU1f1 protein, despite normal levels of Pou1f1 mRNA. Single-cell RNA sequencing of pituitary cells from control female animals indicates that both Msi1 and Pou1f1 mRNAs are expressed in Gh-expressing somatotropes, and immunocytochemistry confirms that Musashi1 protein is present in the somatotrope cell population. We demonstrate that Musashi interacts directly with the Pou1f1 mRNA 3′ untranslated region and exerts translational repression of a Pou1f1 mRNA translation reporter in a leptin-sensitive manner. Musashi immunoprecipitation from whole pituitary reveals coassociated Pou1f1 mRNA. These findings suggest a mechanism in which leptin stimulation is required to reverse Musashi-mediated Pou1f1 mRNA translational control to coordinate AP somatotrope function with metabolic status.